Membumikan Komunikasi Islam dalam Kehidupan Sosial Melalui Warung Kopi di Kota Banda Aceh - Furqan, Furqan; Abdullah, Abdullah; Furqan, Muhammad (Jurnal Keislaman, 2024)
The purpose of this research is to identify and provide understanding and invitation to everyone to ground Islamic communication in social life so that communication patterns between people are well maintained in accordance with the principles of Islamic communication. The research method used is a type of library research. his research is carried out by reading, examining, and analyzing various existing sources, in the form of the Qur'an, Hadith, journals and books, as well as other research results related to communication in social life. The results showed that Islamic communication in social life has a very important role in human life, this can be seen from social meaning, social coverage and social support to being able to limit negative words against someone. Islamic communication is a means of conveying or exchanging information using the principles and methods of communication according to the Qur'an as one of the motivations for Muslims to ground Islamic communication in social life directly and through social media. Meanwhile, in the context of coffee shops as a means of social communication in the city of Banda Aceh, coffee shops are not only a place to drink coffee or rest but also a source of the latest information and also a gathering place for various communities, ranging from ordinary people, community leaders, government employees, and so on. The conclusion is that communication is one of the important reasons in society, of course, in the rules of Islam, besides that Islamic communication and social life play a very large role in the context of coffee shops in the city of Banda Aceh.